Field capture of Thyanta perditor with pheromone-baited traps - Laumann, Raúl Alberto; Blassioli Moraes, Maria Carolina; Khrimian, Ashot; Borges, Miguel (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the field attractiveness of Thyanta perditor synthetic sex pheromone‑baited traps, its attractivity to other stink bug species, and the response of T. perditor to a geometric isomer of the sex pheromone. Two‑liter transparent plastic bottles traps were baited with rubber septa impregnated with the treatments: 1 mg of methyl‑(2E,4Z,6Z)‑decatrienoate [(2E,4Z,6Z)‑10:COOMe], the male sex pheromone of T. perditor; 1 mg of (2E,4Z,6Z)‑10:COOMe protected from sunlight in standard PVC plumbing pipe; 1 mg of its geometric isomer [(2E,4E,6Z)‑10:COOMe]; and traps with rubber septa impregnated with hexane (control). The experiment was carried out in field during the soybean reproductive stages. Traps were monitored weekly, and the captures were compared to the population density estimated by the sampling cloth and visual inspection monitoring techniques. Traps baited with the sex pheromone, protected or not, were more effective in capturing T. perditor than traps baited with the isomer or the hexane. Thyanta perditor sex pheromone showed cross‑attraction to other stink bug species, such as Euschistus heros, Edessa meditabunda, Piezodorus guildinii and Nezara viridula. Pheromone‑baited traps can be used in population monitoring and to identify the relative composition of stink bug guilds.